Colonization of a commercial broiler line by Campylobacter is under limited genetic control and does not significantly impair performance or intestinal health. (5th July 2018) - Bailey, Richard A; Kranis, Andreas; Psifidi, Androniki; Watson, Kellie A; Rothwell, Lisa; Hocking, Paul M; Kaiser, Pete; Stevens, Mark P; Avendano, Santiago
ABSTRACT: Campylobacter is the leading bacterial cause of foodborne diarrheal illness in humans and source attribution studies unequivocally identify handling or consumption of poultry meat as a key risk factor. Campylobacter colonizes the avian intestines in high numbers and rapidly spreads within flocks. A need therefore exists to devise strategies to reduce Campylobacter populations in poultry flocks. There has been a great deal of research aiming to understand the epidemiology and transmission characteristics of Campylobacter in poultry as a means to reduce carriage rates in poultry and reduce infection in humans. One potential strategy for control is the genetic selection of poultry for increased resistance to colonization by Campylobacter . The potential for genetic control of colonization has been demonstrated in inbred populations following experimental challenge with Campylobacter where quantitative trait loci associated with resistance have been identified. Currently in the literature there is no information of the genetic basis of Campylobacter colonization in commercial broiler lines and it is unknown whether these QTL are found in commercial broiler lines. The aim of this study was to estimate genetic parameters associated with Campylobacter load and genetic correlations with gut health and production traits following natural exposure of broiler chickens to Campylobacter . The results from the analysis show a low but significant heritability estimate (0.095 ± 0.037) for C ampylobacter load which indicates a limited genetic basis and that non-genetic factors have a greater influence on the level of Campylobacter found in the broiler chicken. Furthermore, through examination of macroscopic intestinal health and absorptive capacity, our study indicated that Campylobacter has no detrimental effects on intestinal health and bird growth following natural exposure in the broiler line under study. These data indicate that whilst there is a genetic component to Campylobacter colonization worthy of further investigation, there is a large proportion of phenotypic variance under the influence of non-genetic effects. As such the control of Campylobacter will require understanding and manipulation of non-genetic host and environmental factors.